Proceedings of the 2021 ACM SIGSAC Conference on Computer and Communications Security 2021
DOI: 10.1145/3460120.3485250
|View full text |Cite
|
Sign up to set email alerts
|

Search-Based Local Black-Box Deobfuscation: Understand, Improve and Mitigate

Abstract: Code obfuscation aims at protecting Intellectual Property and other secrets embedded into software from being retrieved. Recent works leverage advances in artificial intelligence (AI) with the hope of getting blackbox deobfuscators completely immune to standard (whitebox) protection mechanisms. While promising, this new field of AI-based, and more specifically search-based blackbox deobfuscation, is still in its infancy. In this article we deepen the state of search-based blackbox deobfuscation in three key di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…They treat code as a black box and attempt to reconstruct the original code based on the observable behavior, often represented in the form of input-output samples. Approaches such as SYNTIA [7] and XYNTIA [46] attempt to find an expression with equivalent behavior by relying on a stochastic algorithm traversing a large search space. Other approaches, e. g., QSYNTH [22], are based on enumerative synthesis: they compute large lookup tables of expressions which they use to simplify parts of an expression, reducing its overall complexity.…”
Section: Automated Deobfuscation Attacksmentioning
confidence: 99%
See 4 more Smart Citations
“…They treat code as a black box and attempt to reconstruct the original code based on the observable behavior, often represented in the form of input-output samples. Approaches such as SYNTIA [7] and XYNTIA [46] attempt to find an expression with equivalent behavior by relying on a stochastic algorithm traversing a large search space. Other approaches, e. g., QSYNTH [22], are based on enumerative synthesis: they compute large lookup tables of expressions which they use to simplify parts of an expression, reducing its overall complexity.…”
Section: Automated Deobfuscation Attacksmentioning
confidence: 99%
“…Our deobfuscation tooling is based on MIASM [10] (commit 65ab7b8), TRITON [56] (v. 0.8.1), and SYNTIA [7] (commit e26d9f5). Unfortunately, the code of other automated deobfuscation tools, such as QSYNTH [22], MBA-BLAST [43], or XYN-TIA [46], is not publicly available, preventing us from evaluating them. While NEUREDUCE [29] is available, we found that it crashed on every execution.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 3 more Smart Citations